A Glycosyltransferase-Related Signature for Predicting Overall Survival in Head and Neck Squamous Cell Carcinoma - Wu, Huili; Zhao, Xiao; Zhu, Tingting; Rong, Di; Wang, Ying; Leng, Diya; Wu, Daming (Frontiers in Genetics, 2022)
Background: To establish a prognostic signature based on glycosyltransferase-related genes (GTRGs) for head and neck squamous cell carcinoma (HNSCC) patients. Methods: The prognostic signature of GTRGs was constructed by univariate and multivariate Cox analysis after obtaining the expression of GTRGs from TCGA. A nomogram based on the signature and clinical parameters was established to predict survival of each HNSCC patient. Through gene set enrichment analysis (GSEA), immune cell infiltration, immune checkpoints, immunotherapy and tumor mutational burden (TMB) analysis, potential mechanism was explored. The expression differences and the prognostic efficacy of the signature were verified by Gene Expression Omnibus (GEO) and several online databases. Results: The prognostic signature was constructed based on the five glycosyltransferases (PYGL, ALG3, EXT2, FUT2 and KDELC1), and validated by GSE65858. The pathways enriched between the high- and low-risk groups were significantly different. The high-risk group had higher tumor purity, lower immune cell infiltration, such as CD8+ T cell and Treg, higher cancer-associated fibroblast (CAF) infiltration, lower immune function and lower expression of checkpoints. The signature can also be applied to immunotherapy cohorts to distinguish whether patients benefit from it or not. In addition, the high-risk group had higher TMB and more gene mutation, including TP53, CSMD1, CDKN2A, MUC17, etc. Conclusion: We proposed a prognostic signature based on the glycosyltransferases for HNSCC patients, which may provide potential targets and biomarkers for the precise treatment of HNSCC.